Diverse temporal and spatial mechanisms work, partially through Stanniocalcin-1, V-ATPase and senescence, to activate the extracellular ATP-mediated drug resistance in human cancer cells - Zhang, Haiyun; Song, Jingwen; Ward, Ryan; Han, Yong; Hunt, Arabella; Shriwas, Pratik; Steed, Alexander; Edwards, Cory; Cao, Yanyang; Co, Milo; Chen, Xiaozhuo (Frontiers in Oncology, 2024)
Resistance to drug therapies is associated with a large majority of cancer-related deaths. ATPbinding cassette (ABC) transporter-mediated drug efflux, epithelial-mesenchymal transition (EMT), cancer stem cells (CSCs), glutathione (GSH), senescence, and vacuole-type ATPase (V-ATPase) all contribute to the resistance. We recently showed that extracellular ATP (eATP) induces and regulates EMT, CSC formation, and ABC transporters in human cancer cells and tumors. eATP also consistently upregulates Stanniocalcin-1 (STC1), a gene that significantly contributes to EMT, CSC formation, and tumor growth. We also found that eATP enhances drug resistance in cancer cells through eATP internalization mediated by macropinocytosis, leading to an elevation of intracellular ATP (iATP) levels, induction of EMT, and CSC formation.However, these factors have never been systematically investigated in the context of eATPinduced drug resistance. In this study, we hypothesized that eATP increases drug resistance via inducing ABC efflux, EMT, CSCs, STC1, and their accompanied processes such as GSH reducing activity, senescence, and V-ATPase. RNA sequencing, metabolomics, gene knockdown and knockout, and functional assays were performed to investigate these pathways and processes. Our study results showed that, in multiple human cancer lines, eATP induced genes involved in drug resistance, elevated ABC transporters' efflux activity of anticancer drugs; generated transcriptomic and metabolic profiles representing a drug resistant state; upregulated activities of GSH, senescence, and V-ATPase to promote drug resistance. Collectively, these newly found players shed light on the mechanisms of eATP-induced as well as STC1-and V-ATPase-mediated drug resistance and offer potential novel targets for combating drug resistance in cancers.